Analisis Kepuasan Kerja, Work Life Balance, Motivasi Kerja Terhadap Kinerja Karyawan - Kurniawati, Fitri; Saputra, Wiwin; Jusup, Sri Meike; Purwadisastra, Dikdik; Marjuki, Arif (Jurnal EMT KITA, 2026)
This research aims to determine and analyze the relationship between job satisfaction, work-life balance, and work motivation variables on employee performance. Employee performance can be influenced by various factors, including job satisfaction, work-life balance, and work motivation. Effective strategies are needed to improve employee performance. Using a quantitative approach, data were collected from Millennial Generation employees in various hospitals and analyzed using multiple regression techniques. The data collection technique was by distributing questionnaires to research objects to Millennial Generation employees and through a documentation study of 100 Millennial Generation employees. The findings of this study empirically prove that all three factors can have a significant impact on employee performance, with job satisfaction being the strongest predictor. From the results of this study, partially, the job satisfaction variable has a positive and significant effect on the performance of Millennial Generation employees in various hospitals, the work-life balance variable has a positive and significant effect on the performance of Millennial Generation employees in various hospitals, the work-motivation variable has a positive and significant effect on the performance of Millennial Generation employees in various hospitals. The simultaneous findings show that job satisfaction, work-life balance, and work motivation have a positive and significant effect on the performance of Millennial Generation employees in various hospitals. This research result value of Adjusted R Square was proven to be 45.7%.
Keywords: Employee Performance; Job Satisfaction; Work Motivation; Work Life Balance